Overexpression of KPC contributes to ceftazidime-avibactam heteroresistance in clinical isolates of carbapenem-resistant Klebsiella pneumoniae - Li, Yitan; Chen, Xiandi; Guo, Yingyi; Lin, Yingzhuo; Wang, Xiaohu; He, Guohua; Wang, Mingzhen; Xu, Jianbo; Song, Mingdong; Tan, Xixi; Zhuo, Chao; Lin, Zhiwei (Frontiers in Cellular and Infection Microbiology, 2024)
Ceftazidime–avibactam (CZA) is one of the effective antibiotics used for the treatment of carbapenem-resistant Klebsiella pneumoniae (CRKP) infections, but its resistance rate has increased recently. Previous studies have focused on the mechanisms of CZA resistance, while its heteroresistance in CRKP remains poorly understood. This study aimed to investigate the characteristics and mechanisms of CZA heteroresistance in CRKP isolates. A total of 311 CRKP clinical strains were collected in China from 2020 to 2022. The MICs of CZA and other antibiotics against K. pneumoniae were determined by broth microdilution method. The occurrence of CZA heteroresistance in CRKP was evaluated with population analysis profiling (PAP) and their characteristics were detected by polymerase chain reaction (PCR). The underlying mechanism of CZA heteroresistance in CRKP strains was investigated by molecular sequencing, whole genome sequencing (WGS), quantitative real-time PCR (qRT-PCR), and in vitro functional experiments. Strategies for preventing the emergence of CZA heteroresistance and alternative treatment options for strains exhibiting CZA heteroresistance were further explored. Thirty-four (12.4%) CZA-susceptible CRKP isolates were found to exhibit heteroresistance to CZA. All heteroresistant strains belonged to KPC-2 (97.1%) or KPC-3 (2.9%). The dominant multilocus sequence typing (MLST) was ST11 (64.7%) and the prevalent capsular serotypes were KL47 (38.2%) and KL64 (32.4%). Imipenem-relebactam and meropenem-vaborbactam still exhibited excellent antimicrobial activity against the resistant subpopulations of CZA heteroresistant strains. No significant mutations were found in KPC, OmpK35/36, PBP2/3, and LamB in resistant subpopulations. The relative expression and copy number of blaKPC were significantly upregulated in 47.1% and 35.3% of the resistant subpopulations compared with their parental strains, respectively. Silencing blaKPC expression significantly decreased the CZA MIC in resistant subpopulations with high blaKPC expression and hindered the emergence of CZA heteroresistance in their parental strains. Moreover, increasing the avibactam concentration to 8 or 16 mg/L or combining CZA with 0.5 × MIC tigecycline significantly suppressed the formation of CZA heteroresistance (P<0.05). In conclusion, we identified the occurrence of CZA heteroresistance in CRKP in China, which was attributed to the overexpression of KPC. Increasing the concentration of avibactam or combining CZA with tigecycline could effectively prevent the development of CZA heteroresistance in CRKP isolates. Besides, imipenem-relebactam and meropenem-vaborbactam may serve as alternative therapeutic options when clinical isolates with CZA heteroresistance are detected.